Comparative Efficacy of Neurofeedback Interventions for Attention‐Deficit/Hyperactivity Disorder in Children: A Network Meta‐Analysis - Gang Wu; Qiang He; Da Li; Zhang Zhang; Jinli Miao; Yanping Shu (Brain and Behavior)
ABSTRACT Objective This study aimed to synthesize and encapsulate findings from recent research (May 1, 2018 to August 1, 2023) on neurofeedback interventions for children diagnosed with attention deficit hyperactivity disorder (ADHD). Methods A comprehensive search was conducted across major databases and platforms, including randomized controlled trials s focusing on children aged 5–11 years with ADHD. The inclusion was broad, not restricted by ADHD subtype, gender, IQ, socioeconomic status, or coexisting conditions. Results From the study screening process, 13 studies were included in the network meta‐analysis, involving 1370 children. Most neurofeedback therapies surpassed placebo in ADHD symptoms. In the acceptability outcome, five neurofeedback therapies (HEG, SCP training, TBR training, SMR training, and active control) outperformed the inactive control, physical activity, and EMG therapies. Conclusions The potential efficacy of nonpharmacological interventions in ADHD management among children is illuminated. The findings advocate for a holistic, child‐centered approach, emphasizing the need for further in‐depth research to understand and refine these interventions.